2017
DOI: 10.1371/journal.pone.0188688
|View full text |Cite
|
Sign up to set email alerts
|

Designing a more efficient, effective and safe Medical Emergency Team (MET) service using data analysis

Abstract: IntroductionHospitals have seen a rise in Medical Emergency Team (MET) reviews. We hypothesised that the commonest MET calls result in similar treatments. Our aim was to design a pre-emptive management algorithm that allowed direct institution of treatment to patients without having to wait for attendance of the MET team and to model its potential impact on MET call incidence and patient outcomes.MethodsData was extracted for all MET calls from the hospital database. Association rule data mining techniques wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…This percentage is similar to data in non-orthopaedic patients, 31%, as described by Bergmeir et al 12 16,18,19 with mortality risk reported to be between 5 and 35%. 12,15,18 In our study, a hospital mortality of 8.5% possibly reflected the fact that most cases were due to hypovolaemia, which has been shown to be associated with a lower mortality. 15 Moreover, we analysed only the first RRT activation, and recurrent deterioration after initial stabilisation has been associated with increased mortality.…”
Section: Summary Of Major Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…This percentage is similar to data in non-orthopaedic patients, 31%, as described by Bergmeir et al 12 16,18,19 with mortality risk reported to be between 5 and 35%. 12,15,18 In our study, a hospital mortality of 8.5% possibly reflected the fact that most cases were due to hypovolaemia, which has been shown to be associated with a lower mortality. 15 Moreover, we analysed only the first RRT activation, and recurrent deterioration after initial stabilisation has been associated with increased mortality.…”
Section: Summary Of Major Findingssupporting
confidence: 91%
“…11 The differential diagnosis of postoperative hypotension and its subsequence treatment is challenging. Interestingly, 70% of such patients received an immediate bolus of fluid administration, 12 suggesting that pre-emptive fluid administration may prevent RRT calls. Interestingly, 70% of such patients received an immediate bolus of fluid administration, 12 suggesting that pre-emptive fluid administration may prevent RRT calls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one group recently used routinely collected data from one hospital’s MET experiences to develop pre-emptive management algorithms for common deterioration triggers. 94 Further work in this area could allow some patients to receive initial interventions while rapid responders are en route to the bedside, or even with remote leadership via telemedicine. 95…”
Section: Future Directionsmentioning
confidence: 99%
“…Chan et al 31 investigated whether care-seeking patterns involve the use of healthcare services of various types prior to ED visits and examined the associations of these patterns with the severity of the presenting condition for ED visit and subsequent events. Bergmeir et al 32 aimed to design more efficient, effective, and safe medical emergency team service using ARM techniques.…”
Section: Introductionmentioning
confidence: 99%